Journal of Visualization - Kawahashi, M.; Koyamada, Koji.; Kim, Kyung Chun.; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Visualization is an interdisciplinary imaging science devoted to making the invisible visible through the techniques of experimental visualization and computer-aided visualization. The scope of the Journal is to provide a place to exchange information on the latest visualization technology and its application by the presentation of latest papers of both researchers and technicians. The Journal paper must be the original work of the author(s) and its main part has not been copyrighted, published, accepted or currently being considered for publication elsewhere; and will not be submitted elsewhere for publication under consideration by the Journal of Visualization. The Journal is published quarterly worldwide in English in order to vitalize international studies on visualization and related computer techniques. The journal consists of papers, such as Short Paper, Review Paper, Regular Paper, and Report. The journal is edited by the Editorial Board, composed of the Editor-in-chief, Associate Editors and Advisory Editors. The journal is edited by the Visualization Society of Japan.
Keywords: Computer graphics; Continuum physics; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Fluid mechanics; Engineering Fluid Dynamics; Computer Imaging, Vision, Pattern Recognition and Graphics; Classical and Continuum Physics; Engineering Thermodynamics, Heat and Mass Transfer